Representasi Marxisme dalam Tiga Adegan Film Enola Holmes 2 - Haqqu, Raka Rizca (JIKE : Jurnal Ilmu Komunikasi Efek, 2023)
Social inequality in society is a social issue that is rarely realized by the community because they feel used to it and even cultured with it, even though this social class division is also not an ideology that is embraced and believed by the community. The film Enola Holmes 2, which is a continuation of the first series, has become one of the best-selling films on the Netflix platform with a different storyline compared to other trending films. The purpose of this study is to look at other phenomena that occur apart from the mystery or love story in a film, which is related to the division of social classes and surplus values ??that occur in films where the entire scene is not explained. The research method that is used by researchers is a method with a qualitative approach, John Fiske's semiotics. The researcher assumes that the Marxist movement as socially critical of the capitalists is a breakthrough for the proletariat (workers) not to be complacent in the surplus value that is carried out either openly or covertly.